Refining partial gland ablation for localised prostate cancer: the FALCON project - Rodriguez-Sanchez, Lara; Cathelineau, Xavier; de Reijke, Theo M; Stricker, Phillip; Emberton, Mark; Lantz, Anna; Miñana López, Bernardino; Dominguez-Escrig, Jose Luis; Bianco, Fernando J; Salomon, Georg; Haider, Aiman; Mitra, Anita; et al. (BJU international, 2025)
OBJECTIVES: To provide a contemporary statement on focal therapy (FT) for localised prostate cancer (PCa) from an international and diverse group of physicians treating localised PCa, with the aim of overcoming the limitations of previous consensus statements, which were restricted to early adopters, and to offer direction regarding the various aspects of FT application that are currently not well defined. MATERIALS AND METHODS: The FocAL therapy CONsensus (FALCON) project began with a 154-item online survey, developed following a steering committee discussion and literature search. Invitations to participate were extended to a large, diverse group of professionals experienced in PCa management. From 2022 to 2023, a Delphi consensus study consisting of three online rounds was conducted using the Modified Delphi method. A 1-9 Likert scale was used for the survey, which was followed by an in-person expert meeting. The threshold for achieving consensus was set at 70% agreement/disagreement. Six main aspects of FT were covered: (i) patient selection; (ii) energy source selection; (iii) treatment approach; (iv) treatment evaluation and follow-up; (v) treatment cost and accessibility; and (vi) future perspectives. RESULTS: Of 246 initial participants, 148 (60%) completed all three rounds. Based on participant feedback, 27 new statements were added in the second round, and 33 questions related to personal expertise, for which consensus was not necessary, were excluded. After the third and final round, consensus had not been reached for 69 items. These items were discussed at the in-person meeting, resulting in a consensus of 57 additional items. Consensus was finally not reached on 12 items. Given the volume of data, the voting outcomes are summarised in this article, with a detailed breakdown presented in the form of figures and tables. CONCLUSIONS: The FALCON project delivered a significant consensus on the approach to FT for localised PCa. Additionally, it highlighted gaps in our knowledge that may provide guidance for future research.
Keywords: energy source selection; Delphi study; Delphi Technique; prostate cancer; lidé; treatment evaluation; výběr pacientů; Ablation Techniques; Patient Selection; konsensus; nádory prostaty; delfská metoda; Prostatic Neoplasms; ablation techniques; Consensus; Male; patient selection; consensus; mužské pohlaví; ablace; Humans